El buen trato de los padres y las habilidades socio emocionales en los niños de cinco años de la Institución Educativa Inicial N° 386 Bellavista, Caballococha 2022 - Jordan Lopez de Suarez, Milagros Rosmery (2022)
The objective of the research is to determine the relationship of the good treatment of the parents with the socio-emotional skills of the five-year-old children of the Initial Educational Institution No. 386 Bellavista - Caballo Cocha 2022. The research is basic with a quantitative approach and a non-specific design. experimental of relational scope, the sample consisted of 40 parents with five-year-old children from the studied educational institution, to whom a questionnaire was applied. In the results, a high positive direct relationship (rs= 0.749) was identified between the good treatment of parents and the socio-emotional skills of five-year-old children from the Initial Educational Institution under study. This ordinal relationship was corroborated in the analysis of the hypothesis where it has been shown that there is a significant relationship between the good treatment of parents and socio-emotional skills in five-year-old children of the Initial Educational Institution No. 386 Bellavista, Caballo Cocha 2022 ”.